2013
DOI: 10.14474/ptrs.2013.2.2.87
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physical training on glutamate transporter expression in an experimental ischemic stroke rat model

Abstract: Objective: The present study was aimed at determining the effect of physical training on glutamate transporter activity in a middle cerebral artery occlusion (MCAO)-induced ischemia injury rat model. Design: Randomized controlled trial. Methods: In this study, we randomly divided them into three groups. Group I included non-occlusion sham controls (n=10), Group II included non-physical training after MCAO (n=10), and Group III included rats that were subjected to physical training after MCAO (n=10). Rats in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These authors also identified a significant reduction in the microglial density in the brains of fractalkine/knockout mice receptors (CX3CLI) compared with littermate controls during postnatal weeks 2 to 3; during this period, the dendritic spine density of the hippocampal CA1 pyramidal neurons was significantly enhanced (p < 0.05). These data propose that microglia plays a key roles in the conformational plasticity in development via the fractalkine/fractalkine receptor and the classical complement cascades [10].…”
Section: Neuroglia Relation Among Astrocytes Glutamate and Adenosinementioning
confidence: 89%
See 1 more Smart Citation
“…These authors also identified a significant reduction in the microglial density in the brains of fractalkine/knockout mice receptors (CX3CLI) compared with littermate controls during postnatal weeks 2 to 3; during this period, the dendritic spine density of the hippocampal CA1 pyramidal neurons was significantly enhanced (p < 0.05). These data propose that microglia plays a key roles in the conformational plasticity in development via the fractalkine/fractalkine receptor and the classical complement cascades [10].…”
Section: Neuroglia Relation Among Astrocytes Glutamate and Adenosinementioning
confidence: 89%
“…Physical exercise promotes neural cell survival mechanisms, while suppressing the neural apoptotic tract, for example during stroke by bettering motor enforcement and enhancement the glutamate transporter (GLT-1) expression and activeness, which modifies the neuronal circuitry of the brain [10]. Additional physical exercise increases the neural plasticity and the activity of neural tracts.…”
Section: B F Kania Et Almentioning
confidence: 99%
“…In the rehabilitation field, MMI is generally introduced by using electromyography (EMG) for functional electrical stimulation (FES) control 7 . In previous studies, EMG-controlled FES was mostly applied to muscles of one and the same subject for rehabilitation 8 . Recently, EMG-controlled FES was used in a master-slave paradigm between two persons, indicating as well that MMI can be a feasible information transfer approach for human-to-human control 2 .…”
Section: Introductionmentioning
confidence: 99%